National Registry of Rare Diseases - Yadnil Elizabeth Gómez Vázquez; Onelis Góngora Gómez (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
A rare disease is one that affects a small absolute number of people or a small population. These conditions constitute a significant group of pathologies that, although viewed separately, do not constitute highly prevalent diseases, as a whole they can become a health problem. These diseases affect a quite vulnerable population group because they cause psychological, physical and social damage and constitute a group on which it is necessary to act positively. In Cuba there is no record of the prevalence or incidence of these diseases. It is imperative to create a similar network in Cuba, where these diseases constitute a health problem due to the incidence they have together.